К вопросу о логике соотнесенности требований образовательного стандарта бакалавров в процессном обеспечении деятельности субъектов - Nabiev V. S., Pankratova O. G. (Innovative trends of educational system development, 2017)
deals with topical issues of organizing the activity of subjects of a holistic educational process in the conditions of transition to competency format of diagnosing, monitoring and evaluating results and achievements of students
Keywords: компетентностный подход; pedagogical support; Competence approach; педагогическое обеспечение